Application of Customer Relationship Management Methods for Curtains Sales at Nuel Jaya Curtains Web-Based - Yohana Dela Vega; Afrisawati, Afrisawati; Chitra Latiffani (P3M Politeknik Negeri Bengkalis, 2024)
Web-based curtain sales information system by implementing Customer Relationship Management (CRM) is needed to maintain the stability of existing customers and expand new customers so that sales can continue to increase This study aims to analyze how the application of customer Relationship Management methods at Nuel Jaya Curtains effectively and efficiently in managing relationships with customers, so as to increase sales and customer loyalty. This study uses a qualitative approach with data collection techniques, namely observation, interviews and literature studies, this study evaluates how CRM can make it easier for customers to see products, purchase products, manage customer data, carry out promotional activities, increase more sales, increase profitability at Nuel Jaya Curtains, provide satisfaction to customers about the products offered and features that make it easier for customers. The results showed that the implementation of a web-based CRM system increases the efficiency of managing customer data, improves communication, and supports a more effective sales strategy. These findings emphasize the need for continuous development of CRM systems to maintain competitiveness in the market. Continuous development of CRM systems is essential to maintain competitiveness in a competitive market. In business practice, this means that companies must continuously innovate and adapt their CRM systems to changing customer needs and preferences.